Hospital Admissions for Respiratory Tract Infections in Children Aged 0–5 Years for 2017/2023 - Methi, Fredrik; Størdal, Ketil; Telle, Kjetil; Larsen, Vilde Bergstad; Magnusson, Karin (Frontiers in Pediatrics, 2022)
Aim: To compare hospital admissions across common respiratory tract infections (RTI) in 2017-21, and project possible hospital admissions for the RTIs among children aged 0–12 months and 1-5 years in 2022 and 2023. Methods: In 644 885 children aged 0–12 months and 1–5 years, we plotted the observed monthly number of RTI admissions [upper- and lower RTI, influenza, respiratory syncytial virus (RSV), and COVID-19] from January 1st, 2017 until October 31st, 2021. We also plotted the number of RTI admissions with a need for respiratory support. We used the observed data to project four different scenarios of RTI admissions for the rest of 2021 until 2023, with different impacts on hospital wards: (1) “Business as usual,” (2) “Continuous lockdown,” (3) “Children's immunity debt,” and (4) “Maternal and child immunity debt.” Results: By October 31st, 2021, the number of simultaneous RTI admissions had exceeded the numbers usually observed at the typical season peak in January, i.e., ~900. Based on our observed data and assuming that children and their mothers (who transfer antibodies to the very youngest) have not been exposed to RTI over the last one and a half years, our scenarios suggest that hospitals should be prepared to handle two to three times as many RTI admissions, and two to three times as many RTI admissions requiring respiratory support among 0–5-year-olds as normal, from November 2021 to April 2022. Conclusion: Scenarios with immunity debt suggest that pediatric hospital wards and policy makers should plan for extended capacity.